2004
DOI: 10.1097/01.shk.0000095935.86703.ca
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Novel Thromboxane A2 Inhibitor on Right Ventricular-Arterial Coupling in Endotoxic Shock

Abstract: We investigated the effects of a dual thromboxane (TX)A2 synthase inhibitor and TXA2 receptor antagonist (BM-573) on right ventricular-arterial coupling in a porcine model of endotoxic shock. Thirty minutes before the onset of 0.5 mg/kg endotoxin infusion, six pigs (Endo group) received an infusion with a placebo solution, and six other pigs (Anta group) with BM-573. Right ventricular pressure-volume loops were obtained by the conductance catheter technique. The slope (Ees) of the end-systolic pressure-volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
4
5
0
2
Order By: Relevance
“…To assess the independent effects of BM-573 on right ventricular hemodynamics, we measured the hemodynamic parameters in five pigs without embolism before and every 30 min after BM-573 infusion until 240 min, and in five sham-operated control animals during the same time interval. In accordance with previous studies by our group (Rolin et al, 2003;Lambermont et al, 2004), comparison of time course evolution revealed no effect of BM-573 on mean blood flow, heart rate, aortic blood pressure, R 1 , R 2 , L, E a , end-diastolic volume, E es , E es /E a ratio, and efficiency. The only difference noticed was that the increase in mean PAP with time was slightly greater in the sham-operated control animals (from 10.8 Ϯ 1.4 to 15.5 Ϯ 2.1 mm Hg) than in the group receiving BM-573 (from 14.33 Ϯ 1.03 to 16.49 Ϯ 0.9 mm Hg).…”
Section: Effects Of Bm-573 On Hemodynamic Parameters In Pigs Without supporting
confidence: 71%
See 1 more Smart Citation
“…To assess the independent effects of BM-573 on right ventricular hemodynamics, we measured the hemodynamic parameters in five pigs without embolism before and every 30 min after BM-573 infusion until 240 min, and in five sham-operated control animals during the same time interval. In accordance with previous studies by our group (Rolin et al, 2003;Lambermont et al, 2004), comparison of time course evolution revealed no effect of BM-573 on mean blood flow, heart rate, aortic blood pressure, R 1 , R 2 , L, E a , end-diastolic volume, E es , E es /E a ratio, and efficiency. The only difference noticed was that the increase in mean PAP with time was slightly greater in the sham-operated control animals (from 10.8 Ϯ 1.4 to 15.5 Ϯ 2.1 mm Hg) than in the group receiving BM-573 (from 14.33 Ϯ 1.03 to 16.49 Ϯ 0.9 mm Hg).…”
Section: Effects Of Bm-573 On Hemodynamic Parameters In Pigs Without supporting
confidence: 71%
“…After sterile filtration, the solution was administrated intravenously (10 mg/kg/h), leading to a steady state. This dosage has been chosen according to previous pharmacokinetic studies realized with BM-573 (Rolin et al, 2003;Dogne et al, 2004;Lambermont et al, 2004). The second group (placebo group; n ϭ 6) was perfused with equivalent volume of the same vehicle but without BM-573.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Here, we describe in vitro and in vivo pharmacological characterization of BM-613, a novel dual TXRA and TXSI developed in our laboratory. It is a close derivative of BM-573, another TXRA and TXSI described in the literature Dogné et al, 2004b;Ghuysen et al, 2004;Lambermont et al, 2004).…”
Section: Bm-613 An Original Antiplatelet and Antithrombotic Agent 297mentioning
confidence: 99%
“…1), a new TXA 2 modulator synthesized in our laboratory. BM-613 is a chemical derivative of BM-573, another thromboxane modulator combining TXRA and TXSI activities that has been widely described in literature Dogné et al, 2004b;Ghuysen et al, 2004;Lambermont et al, 2004). BM-613 has been developed as a dual TXRA and TXSI characterized by high activity on platelets compared with smooth muscle.…”
mentioning
confidence: 99%
“…En outre, la détermination du couplage ventriculoartériel permet d'apprécier l'efficience du transfert d'énergie du myocarde vers le système arté-riel. Au plan expérimental, il est bien établi que le couplage ventriculoartériel est altéré dans l'infarctus du myocarde, l'embolie pulmonaire et le choc septique [23][24][25][26]. La restauration d'un couplage ventriculoartériel optimal par voie pharmacologique est possible dans certaines de ces pathologies [23][24][25][26].…”
Section: Intérêt Clinique Du Couplage Ventriculoartérielunclassified